Developmental outcomes in Japanese preschool‐age children conceived through assisted reproductive technology. Issue 11 (4th August 2022) - Aoki, Sayaka; Hashimoto, Keiji; Ogawa, Kohei; Horikawa, Reiko; Sago, Haruhiko
Abstract: Aim: This study aimed to investigate the developmental outcomes of Japanese babies conceived through assisted reproductive technology (ART), born at ages 48 and 60 months. Methods: Data were collected from 725 children in a hospital‐based cohort study conducted in Japan. The children's level of development was assessed using the Kinder Infant Development Scale, a parent‐rated questionnaire that consists of nine developmental domains. We compared the development between children conceived through ART ( N  = 189) and those conceived naturally ( N  = 536) by conducting analyses of covariance. For the analyses, we controlled for the effects of maternal age, family income, parental education, and multiple births. Results: At 48 months, no significant difference was found between children conceived through ART and those conceived naturally, except for the development of receptive language ( F (1, 718) = 4.869, p  = 0.028)), which was found only for boys. The mean developmental age of receptive language was 60.1 for the children conceived through ART and 57.5 for those conceived naturally. At 60 months, no significant difference was found between children conceived through ART and those conceived naturally, in all domains. Conclusion: At ages 48 and 60 months, no significant difference was found between the children conceived through ART and those conceived naturally in nine developmental domains, except for boys' receptive language at 48 months.